DISPARITAS PEMBANGUNAN EKONOMI ANTAR KABUPATEN/KOTA DI PROVINSI SULAWESI UTARA - Irene Rumagit; Olly E. H. Laoh; Martha M. Sendow; Lorraine W. Th. Sondak (Universitas Sam Ratulangi, 2014)
ABSTRACTIrene Rumagit . Disparities between the Economic Development Districtand Cities North Sulawesi ( Under the guidance of H. O. Esry Laoh as chairman ,M. Sendow and L.W.Th Sondak as a member ) .The objective of this research is to assess the economic developmentdisparities among districts and cities in North Sulawesi in 2007 - 2012 period .This research is motivated by the diversity of natural resources and demographicconditions , differences in income per capita and economic growth contained ineach regency and town in North Sulawesi. As a result of these differences , theability to increase economic development is different from one region to the otherregion.The data collection took place during two months from September toOctober 2013 . The data used are per capita GDP , population data and growthdata obtained from the Central Statistics Agency of North Sulawesi province .Analysis of the data in the form of descriptive analysis are presented in tables andquadrant by using analytical tools Williamson Index.The results showed that the economic development district and cities inthe province of North Sulawesi during the period 2007 - 2012 continues toinequality , where the data is used proved that there are significant differencesamong the districts and cities in North Sulawesi . Results proficiency level couldbe seen clearly when analyzed by Williamson index which indicates that the rateof economic development was still classified inequality on inequality of economicdevelopment . This was due to the diversity of potential and natural resourcesamong districts and cities that led to per capita income and economic growthbecomes different resulting imbalance of economic development.